ANALYSIS OF LOCUTIONARY, ILLOCUTIONARY, AND PERLOCUTIONARY ACTS IN THE “TUMBLER TUKU” THREADS CASE - Riska Moriska; Nadira Azzahra; Nafisa Aulia Putri Pakpahan; Randi Simarmata; Jonnes Naibaho; M. Oky Fardian Gafari; Herning Puspitarini (LP2M UIN Abdul Muthalib Sangadji Ambon, 2026)
Abstract This study is motivated by the widespread use of language on social media, which serves not only as a means of conveying information but also as a vehicle for social action capable of shaping public opinion. The “Tumbler Tuku” case on the Threads platform exemplifies a digital communication phenomenon that elicited diverse responses from netizens due to differing interpretations of the utterances. This study aims to analyze the forms and functions of locutionary, illocutionary, and perlocutionary speech acts in posts and comments related to this case. The method used is a qualitative descriptive approach. The data consisted of utterances collected through observation and note-taking. These data were then analyzed based on speech act classification while considering the communicative context. The results indicate that locutionary speech acts are not entirely neutral, as they contain framing elements that can shape the audience’s initial perceptions. Illocutionary speech acts reveal differing communication strategies among speakers, such as expressions of disappointment, accusations, admissions, and commitments as efforts toward conflict resolution. Meanwhile, perlocutionary speech acts demonstrate diverse impacts, ranging from support and criticism to reflective evaluation, indicating that the meaning of utterances is dynamic and influenced by the audience’s perspective. Thus, this study confirms that language on social media plays a significant role in shaping meaning and public opinion. Keywords: speech acts; pragmatics; social media; threads; public opinion